Penguatan Nilai-nilai Pancasila dalam Membentuk Karakter Unggul Taruna di Politeknik Pelayaran Sorong - Permady, Gigieh Cahya; Zulfikar, Gilang; Wahyuni, Reza; Sandra, Ika (JOM, 2024)
This study aims to analyze Pancasila education in the Politeknik Pelayaran Sorong. The study used a qualitative research method with a descriptive format. Data collection is accomplished by observation, analysis, and documentation. The findings indicate that the effectiveness of Pancasila education at Politeknik Pelayaran Sorong is achieved through interactive and holistic teaching that integrates theory and practice through systematic and structured learning processes, such as the lesson plan (RPS), the use of effective learning methods, and comprehensive teaching methods, such as lectures, discussion, and case studies. It ensures that students fully internalize Pancasila values and contributes to character development. This method not only assists them in understanding the theoretical aspects of Pancasila, but it also helps them to apply them in their daily lives. This learning process is effective because it incorporates fundamental principles such as integrity, empathy, critical thinking, communication skills, and collaboration. As a result, Taruna has an excellent personality and is willing to face challenges with inclusive.